Problematika Pembelajaran Bahasa Arab Menggunakan Film Di MTs Al Hikmah Cikoneng - Yunus, Machmud; Nurlatifah, Nurlatifah (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2023)
This research aims to find out what problems students face in class VIII at MTs Al – Hikmah Cikoneng when learning Arabic using Arabic film media. In addition, this study aims to look at opportunities and solutions for Arabic teachers to find new methods of teaching Arabic using film media. This study used a qualitative research method with a descriptive approach. Where this research is research that requires information, explanations, and oral information. The research instruments are observations, interviews, and documentation. The results of this study indicate that the problems faced by students when learning Arabic using film are films that are less interesting in terms of animation and graphics, inadequate subtitles, dialogues that are too fast, and mufrodat that are difficult to memorize. In addition, their learning motivation is still low in learning Arabic so that there are still many students who are not fluent in reading Arabic sentences, which causes their listening skills or maharotul istima' to be still relatively low.